The Role of Career Development, Work Environment and Compensation in Improving Employee Performance PT Bridgestone Tire Indonesia Bekasi - Suryanto Suryanto; Yohanes Ferry Cahaya (Perbanas Institute, 2023)
This study aims to analyze the effect of career development, work environment and compensation on the performance of PT Bridgestone Tire Indonesia Bekasi employees. The free variables used are career development, work environment and compensation while the bound variables of this study are employee performance. This research method uses quantitative methods with a total sample of 71 respondents. The analysis technique used in the study is a regression test. The results of this study can be concluded that the variables of career development and work environment do not have a significant effect on employee performance , while the compensation variable has a significant effect on employee performance.